(3GdGMUGA aj GdefGgL GdHMKjI (B:s (3GdJQHhjI hGdfaSjI (B/s - (3GdHOQj, WGQbs; (3fLe, SgjdIs ((3YeGf(B: s (3OGQ GdKbGaI ddfTQ(B, s, 2008)
(3GdeMJhjGJ (B: (3GdebOeI(B-(3GdaUd GdChd (B: (3eaGgje MOjKI aj CgejI GdEMUGA GdJQHhj (B: (3eaghe YGe ddEMUGA (B: (3GdWQjbI GdYdejI GdefgLjI ddHMK GdYdej (B: (3GdEMUGA cCSdhH efgLj (B: (3UjGZI GdHMK GdYdej (B: (3COhGJ GdHMK GdYdej heUGOQ GdMUhd Ydi GdeYdheGJ hGdHjGfGJ (B: (3JHhjH GdeYdheGJ hGdHjGfGJ GdEMUGFjI (B: (3JUeje GdGSJeGQGJ GdEMUGFjI hGdJaQjZ GdEMUGFj (B: (3JaQjZ HjGfGJ GdGSJeGQGJ GdEMUGFjI(B-(3GdaUd GdKGfj (B: (3GdGSJNOGeGJ GdHjGfjI GdEMUGFjI (B: (3CgejI GdQShe GdHjGfjI (B: (3GdQShe GdHjGfjI aj MGdI Gdbje GdeHhHI (B((3GdefaUdI(B) : (3GdQShe GdHjGfjI aj MGdI Gdbje GdeHhHI (B((3GdeJUdI(B) : (3GdeLJeY GdEMUGFj (B: (3eaghe GdYjfGJ (B: (3JUeje GdYjfGJ (B: (3CfhGY GdYjfGJ (B: (3CNWGA GNJjGQ GdYjfGJ(B-(3GdaUd GdKGdK (B: (3GdEMUGA GdGSJOdGdj (B: (3GNJHGQGJ GdOGdI GdEMUGFjI (B: (3GdaQhV GdEMUGFjI (B: (3GdaQjVI GdUaQjI (B: (3eQHY cGj (B: (3OQLGJ GdMQjI (B: (3GNJHGQ (B((3J(B) (3SJhOfJ (B: (3GdCQbGe GdbjGSjI (B: (3GdSdGSd GdRefjIs
(3HjHdjhZQGajG(B: (3U(B. 207s
Keywords: (3GdGMUGAs; (3GdHMhK GdJQHhjIs; (3WQb GdHMKs; (3Yde GdfaS GdJQHhj(B- (3GdWQb GdEMUGFjI s